Pengaruh Iklan Televisi Teh Botol Sosro Versi “Semeja Bersaudara” Dan Iklan Instagram Versi “Serunya Jalan Terus” Terhadap Citra Merek - Nurul Fitria Ningsih; Euis Komalawati; Angelika Rosma (LUGAS Jurnal Komunikasi, 2019)
This study aimed to determine the effect of Television Advertisement Version “Semeja Bersaudara” And Instagram Advertisement Version “Serunya Jalan Terus” On Teh Botol Sosro Brand Image. The study method used is quantitative methods. Data collection techniques used in the questionnaire form and literature. The population of this study from STIAMI Institute student. The sampling technique in this research is nonprobability sampling with the accidental sampling method. A sample of 100 samples has been obtained. The data analysis used is multiple linear regression analysis using IBM Statistic version 22. The results showed that the Television Advertisement Version “Semeja Bersaudara” has an influence on Brand Image Teh Botol Sosro of 44,3%. Instagram Advertisement Version “Serunya Jalan Terus” has an influence on Brand Image Teh Botol Sosro of 40,1%. Television Advertisement Version “Semeja Bersaudara” and Instagram Advertisement Version “Serunya Jalan Terus” significantly influence on Teh Botol Sosro Brand Image. Television Advertisement Version “Semeja Bersaudara” and Instagram Advertisement Version “Serunya Jalan Terus” affect the variants of Teh Botol Sosro Brand Image simultaneously with value 0f 0,471 or 47,1% and there are 52,9% other unexplained factors not included in this study.